2021
DOI: 10.1088/1742-6596/1722/1/012109
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of the discovery model based on numbered head together reviewed from students’ cognitive style in mathematics learning

Abstract: Students consider that mathematics learning delivered by the teacher to be very boring, teacher-centered learning and most students said that mathematics difficult to understand. For this reason, this study aims to analyze the implementation of the discovery model based on NHT in mathematics learning in terms of students’ cognitive styles. This study uses a quantitative approach with a quasi experimental research design. The population in this study were all 7th grade students of SMP Karangmalang Sragen. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
2
1
2
Order By: Relevance
“…The results of this study have shown another development that cognitive style does not always have a linear effect on various human learning performances in aspects of cognitive behaviour. This finding contradicts the findings of previous studies that examined differences in cognitive style on mathematics achievement in terms of gender [5], [6], [21], which showed that cognitive style factors were one of the differentiating aspects in mathematics learning performance between men and women.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results of this study have shown another development that cognitive style does not always have a linear effect on various human learning performances in aspects of cognitive behaviour. This finding contradicts the findings of previous studies that examined differences in cognitive style on mathematics achievement in terms of gender [5], [6], [21], which showed that cognitive style factors were one of the differentiating aspects in mathematics learning performance between men and women.…”
Section: Discussioncontrasting
confidence: 99%
“…Various studies exploring the impact of cognitive style on learning have yet to show consistent results. Researches show that cognitive style generally affects memory performance [4] and learning achievement in mathematics [5], [6]. However, the answer to the question: of which cognitive style is more supportive of academic achievement is varied and inconsistent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pembelajaran menulis esai menggunakan kooperatif NHT dapat meningkatkan hasil belajar mahasiswa, hal ini menunjukan bahwa pembelajaran kooperatif NHT efektif untuk diterapkan dalam belajar. Peningkatan hasil belajar menggunakan kooperatif NHT juga terjadi pada penelitian yang dilakukan oleh peneliti sebelumnya tentang efektivitas penggunaan model kooperatif NHT (Setyaningsih & Utami, 2021;Sri Puji Retno et al, 2021;Wahyuni, 2019).…”
Section: Pembahasanunclassified
“…(Paba et al, 2020) Hasil belajar merupakan tolak ukur pemncapaian siswa dalam pembelajaran dan diperoleh dari hasil evaluasi dalam proses belajar yang diperoleh melalui tes untuk melihat tingkat capaian kemampuan siswa. (Setyaningsih & Utami, 2021) menjelaskan hasil belajar merupakan hasil dari proses belajar dan pembelajaran melalui evaluasi agar mampu melihat tingkat kemampuan akademik.…”
Section: Pendahuluanunclassified